Rhizospheric bacteria: the key to sustainable heavy metal detoxification strategies - Joshi, Samiksha; Gangola, Saurabh; Bhandari, Geeta; Bhandari, Narendra Singh; Nainwal, Deepa; Rani, Anju; Malik, Sumira; Slama, Petr (Frontiers in Microbiology, 2023)
The increasing rate of industrialization, anthropogenic and geological activities have expedited the release of heavy metals (HMs) at higher concentration in environment. HM contamination resulting due to its persistent nature, injudicious use poses a potential threat by causing metal toxicities in humans and animals as well as severe damage to aquatic organisms. Bioremediation is an emerging and reliable solution for mitigation of these contaminants using rhizospheric microorganisms in an environmentally safe manner. The strategies are based on exploiting microbial metabolism and various approaches developed by plant growth promoting bacteria (PGPB) to minimize the toxicity concentration of HM at optimum levels for the environmental clean-up. Rhizospheric bacteria are employed for significant growth of plants in soil contaminated with heavy metal. Exploitation of bacteria possessing plantbeneficial traits as well as metal detoxifying property is an economical and promising approach for bioremediation of heavy metal. Microbial cells exhibit different mechanisms of HM resistance such as active transport, extra cellular barrier, extracellular and intracellular sequestration and reduction of HM.Tolerance of HM in microorganisms may be chromosomal or plasmid originated. Proteins such as MerT and MerA of mer operon and czcCBA, ArsR, ArsA,ArsD, ArsB, and ArsC genes are responsible for metal detoxification in bacterial cell. This review gives insights about the potential of rhizospheric bacteria in HM removal from various polluted areas. In addition, it also gives deep insights about different mechanism of action expressed by microorganisms for HM detoxification. The dual-purpose use of biological agent as plant growth enhancement and remediation of HM contaminated site is the most significant future prospect of this article.